Subkutana dostava terapevtskih proteinov in peptidov - Gosenca Matjaž, Mirjam (Farmacevtski vestnik, 2024)
The intensive development in the field of biological active substances, which are characterized by high specificity, improved therapeutic efficiency and fewer adverse effects, is reflected in the rapidly growing number of biological medicinal products on the market. Recently, the subcutaneous application of biological medicines has become a valuable alternative to intravenous administration for many diseases. The reasons for this are manifold and are primarily related to the numerous benefits for both the patient and the healthcare system, with the possibility of self-injection in the home environment being one of the most important. The article presents biological medicinal products with therapeutic peptides and proteins from the point of view of subcutaneous application. Thus, the development in the field of therapeutic peptides is moving towards delivery systems for subcutaneous application (polymeric microparticles, implants, and in situ gelling polymer solutions and liquid crystals), that allow sustained release for up to several months. Subcutaneous injection of high doses of monoclonal antibodies can be achieved by highly concentrated formulations with appropriate viscosity or by applying a larger volume of solution using modern containers/devices. In parallel, great progress has been made in the use of recombinant human hyaluronidase, which temporarily modifies the subcutaneous tissue so that a larger volume of solution can be applied.
Keywords: biological medicinal products; Biološka zdravila; monoclonal antibodies; monoklonska protitelesa; peptides; peptidi; subcutaneous application; subkutana aplikacija